The efficacy of colchicine in patients with gout with different missense genetic variants of the ABCG2 gene (V12M; rs2231137 and Q141K; rs2231142) - M. S. Eliseev; M. N. Chikina; I. A. Guseva; O. V. Zhelyabina; Ya. I. Kuzmina (Современная ревматология)
Genetic polymorphisms in ABCG2 gene (V12M; rs2231137 and Q141K; rs2231142) in patients with gout may determine the efficacy of colchicine for the prevention of arthritis attacks during the initiation of urate-lowering therapy. These data can be used in the development of a personalized approach for the treatment of patients with gout.Objective: to evaluate the efficacy of colchicine in patients with gout with different missense genetic variants of the ABCG2 gene (V12M; rs2231137 and Q141K; rs2231142).Material and methods. The study included 96 patients with gout who were randomized into the following groups: combined therapy with colchicine (Colchicine LIRKA) 0.5 mg/day and febuxostat 80 mg/day; colchicine (Colchicine LIRKA) 1.0 mg/day and febuxostat 80 mg/day; monotherapy with febuxostat 80 mg/day. The dosage adjustment of febuxostat and the assessment of the tolerability of the therapy were carried out in accordance with the Russian recommendations for the treatment of gout.Genotyping of the ABCG2 gene polymorphisms (V12M; rs2231137 and Q141K; rs2231142) was performed in all patients. Patients were observed for 6 months; we compared the frequency of arthritis attacks and the intensity of pain according to the visual analogue scale (VAS) for different genotypes of the polymorphism 421C>A of the ABCG2 gene (rs2231142) and for the polymorphism V12M of the ABCG2 gene (rs2231137).Results and discussion. 64% of patients had an CC genotype, 31% had the CA genotype and 5% had the AA genotype of polymorphism 421C>A of the ABCG2 gene (rs2231142). No significant differences in the frequency of arthritis flares (mean 0.3±0.7 and 0.6±1.0; p=0.2) and pain intensity during arthritis according to VAS (56.8±17.2 and 57.3±22.9 mm, respectively; p=0.9) were observed in carriers of the CC and CA/AA genotypes during the 6-month observation period. In the presence of the V12M polymorphism of the ABCG2 gene (rs2231137) 89% of patients had CC genotype and 11% had CT genotype. In carriers of the CC and CT genotypes, the frequency of arthritis flare-ups (median 0.4±0.9 and 0.7±0.8; p=0.3) and the intensity of pain according to VAS (56.8±19.7 and 67.5±18.5 mm, respectively, p=0.3) did not differ significantly.Conclusion. Colchicine reduces the risk of arthritis flare-ups development. However, the hypothesis of a correlation between the inefficacy of the drug and the presence of different ABCG2 genotypes (V12M; rs2231137 and Q141K; rs2231142) was not confirmed.